Design and stepwise user evaluation of an ergonomic 2 DOF arthroscopic cutter. Issue 1 (1st January 2017) - Horeman, Tim; Kment, Christoph; Kerkhoffs, Gino M.M.J.; Tuijthof, Gabriëlle J.M.
Abstract: The goal of this study was to determine the preferred handle design for two degrees of freedom steerable arthroscopic cutter by performing a two-step development approach. The expected usefulness and usability of control components of three entirely different handles were defined by an on-line survey with 101 students and the actual control by a standardised laboratory study with mock-up models by 16 students. The preferred handle design was integrated in a full functional prototype and optimized by 10 experts performing a meniscectomy on human cadaver knees. Students (survey 70% and task 91%) expected the same control behaviour as the experts (60%): steering a wheel to the right should evoke tip steering to the right regardless the orientation of the beak and moving a ring lever towards the handle's centre point should evoke closure of the tip. Development of surgical instruments can benefit from expected control behavior based on daily life tools, but requires expert involvement for specific surgical tasks and context.